2020
DOI: 10.1088/2053-1591/ab94fb
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen in the properties of diamond-like carbon (DLC) coating on Ti6Al4V substrate

Abstract: The great interest in the study of diamond-like carbon films (a-C:H) is justified by its mechanical and tribological properties. However, the high internal stress of the film results in its difficult adhesion to the metallic substrate, which can be solved by nitrogen incorporation in the a-C:H film, allowing a formed film of lower internal stress. The objective of this work is to evaluate the influence of flow (20, 30 and 40sccm), CH 4 /Ar ratio (90/10 and 70/30) and voltage (400, 500, 600 and 700 V) in the a-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 56 publications
(83 reference statements)
3
19
1
Order By: Relevance
“…The raw and fitted peaks of C 1s spectra of different specimens are shown in Figure 3a-f. The standard core level binding energies (BE) of sp 2 C=C, sp 3 C-C, and C-O bonds are 284.4 ± 0.2, 285.2 ± 0.2 and 286.5 ± 0.3 eV, respectively [6,12,19]. During fitting, the fitted BE deviated slightly from the above ideal value probably due to the collective effect of the chemical environment, defect density, together with residual stress [17].…”
Section: Chemical Bondingmentioning
confidence: 98%
See 2 more Smart Citations
“…The raw and fitted peaks of C 1s spectra of different specimens are shown in Figure 3a-f. The standard core level binding energies (BE) of sp 2 C=C, sp 3 C-C, and C-O bonds are 284.4 ± 0.2, 285.2 ± 0.2 and 286.5 ± 0.3 eV, respectively [6,12,19]. During fitting, the fitted BE deviated slightly from the above ideal value probably due to the collective effect of the chemical environment, defect density, together with residual stress [17].…”
Section: Chemical Bondingmentioning
confidence: 98%
“…The variation of hardness with DCT temperature agree with the above change of I D /I G and sp 2 /sp 3 bond ratios. Because specimens with or without DCT kept almost the same residual stress, and the nano-indention depth was less than 1/8 thickness of the DLC coatings, thus, the hardness improvement of EM-140 surely was responsible for sp 3 C fraction enhancement [2,12,20]. One hand, the mechanical and micro-structural change of EM 35 alloy substrate induced by DCT [34,35,37] provided strong support for the coating; another hand, the sp 2 /sp 3 C ratio of the coating affected the interface strength between DLC and the interlayer.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, the deposition of a silicon-based layer was carried out, using hexamethyldisiloxane (HMDSO) as a precursor, with 70% HMDSO and 30% Ar at a total gas pressure of 0.06 torr for 15 min. Then, the deposition of the DLC or DLC(N) films was carried out with the parameters based on the study carried out by Almeida et al 19 . The substitution of argon for nitrogen in the gas mixture for the DLC(N) films followed the studies carried out by Franceschini and Freire 25 and Franceschini, Freire and Silva 16 .…”
Section: Deposition Of the Filmsmentioning
confidence: 99%
“…Several works report the effect of the DLC doping on their property modification using different elements [12][13][14][15][16][17][18] , such as nitrogen that added to DLC films can considerably improve its adhesion to metallic substrates 19 , with a great influence on the effectiveness of corrosion protection and wear resistance of the treated material 20,21 . Almeida et al 21 observed that the introduction of intermediate amounts of N 2 (30%) on the DLC film by PECVD reduces the fraction of sp 3 bonds *e-mail: solano.larissa@gmail.com keeping the mechanical characteristics of the DLC film, and improving the wear and adhesion of the film to the metallic substrate.…”
Section: Introductionmentioning
confidence: 99%